Discoidin Domain Receptors: Unique Receptor Tyrosine Kinases in Collagen-mediated Signaling - Fu, Hsueh-Liang (American Society for Biochemistry and Molecular Biology, 2013)
The discoidin domain receptors (DDRs) are receptor tyrosine kinases that recognize collagens as their ligands. DDRs display unique structural features and distinctive activation kinetics, which set them apart from other members of the kinase superfamily. DDRs regulate cell-collagen interactions in normal and pathological conditions and thus are emerging as major sensors of collagen matrices and potential novel therapeutic targets. New structural and biological information has shed light on the molecular mechanisms that regulate DDR signaling, turnover, and function. This minireview provides an overview of these areas of DDR research with the goal of fostering further investigation of these intriguing and unique receptors.